Indonesia betrayed how development fails - Collins, Elizabeth Fuller (University of Hawaii Press, 2007)
Supporters of neoliberalism claim that free markets lead to economic growth, and the establishment of democratically accountable governments. This book offers a view from Sumatra of the realities behind the debates during the final years of Suharto's New Order and the beginning of a transition to more democratic government.